The Key To Successful Early Childhood Educators: Performance Study of The Raudhatul Athfal (RA) Teacher in Yogyakarta. - Fu`ad Arif Noor (Universitas Muhammadiyah Ponorogo, 2020)
This research is to find out how to improve the performance of RA teachers who excel in Yogyakarta so that it is the key to its success. This research is a qualitative research through a psychological approach that is carried out directly to the object under study, to obtain data relating to aspects of teacher performance so that the performance improvement is an example for other teachers. Data collection methods using interviews, documentation, and observation. The results revealed that to improve the performance of outstanding RA teachers through 6 (six) steps undertaken by outstanding RA teachers, namely: 1) Knowing there are still shortcomings in performance, 2) Knowing weaknesses and shortcomings in the seriousness of teaching, 3) Identifying what becomes causes of deficiency especially those related to performance itself, 4) Develop a performance plan that is presented, 5) Assessing the problem has been resolved or not (problem solving), 6) Starting from the beginning again, if needed and needed again.